Satisfaction with health services received by patients in regional hospitals using SERVQUAL - Aniharyati, Aniharyati; Haris, Abdul; Lalu, Sulaiman; Saimi, Saimi; Menap, Menap; Sastrawan, Sastrawan (International Journal of Public Health Science (IJPHS), 2025)
The concept of patient satisfaction, which has historically been overlooked and undervalued, is gaining importance. We aimed to investigate patient satisfaction with health services at the hospital. This cross-sectional study was conducted between January and June 2024. The study was conducted at Bima City Regional Hospital, NTB, Indonesia. The sample obtained was 437. The level of satisfaction was measured using 19 questions. Chi-square test and logistic regression were used in this study. The highest opportunity for reliability and responsiveness was found in patients aged 20–29 with OR and CI values of 1.97 (1.65–2.98) and 1.76 (1.03–2.09), respectively. For the tangibles dimension, the highest opportunity was in the age of 40-49 with OR and CI values of 1.98 (2.03–4.37). The highest OR (CI) values for each employed status namely 0.96 (0.77–1.21), 0.89 (0.67–1.18), 0.76 (0.41–1.40), 0.79 (0.51–1.70), and 0.92 (0.72–1.23). Meanwhile, at the level of education, respondents with university education had the highest opportunity value in all dimensions, with OR and Ci values of 0.84 (0.58–1.34), 1.42 (0.78–2.51), 0.51 (0.19–1.56), 0.59 (0.22–1.67), 1.45 (0.82–2.87). In conclusion, patient satisfaction with health services was influenced by age, employment status, and provider friendliness.